2014
DOI: 10.1017/jfm.2014.508
|View full text |Cite
|
Sign up to set email alerts
|

Stability of flow in a channel with longitudinal grooves

Abstract: The travelling wave instability in a channel with small-amplitude longitudinal grooves of arbitrary shape has been studied. The disturbance velocity field is always three-dimensional with disturbances which connect to the two-dimensional waves in the limit of zero groove amplitude playing the critical role. The presence of grooves destabilizes the flow if the groove wavenumber β is larger than β tran ≈ 4.22, but stabilizes the flow for smaller β. It has been found that β tran does not depend on the groove ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Analysis of the transient growth demonstrated that optimal disturbances have the form of streamwise vortices (Szumbarski & Floryan 2006). Moradi & Floryan (2014) investigated the effects of longitudinal grooves (grooves parallel to the flow direction) and documented changes in the characteristics of the TS waves. They were able to demonstrate that short-wavelength grooves destabilize such waves while long-wavelength grooves stabilize them, when compared with their behaviour in a smooth channel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the transient growth demonstrated that optimal disturbances have the form of streamwise vortices (Szumbarski & Floryan 2006). Moradi & Floryan (2014) investigated the effects of longitudinal grooves (grooves parallel to the flow direction) and documented changes in the characteristics of the TS waves. They were able to demonstrate that short-wavelength grooves destabilize such waves while long-wavelength grooves stabilize them, when compared with their behaviour in a smooth channel.…”
Section: Resultsmentioning
confidence: 99%
“…The problem formulation has been described in detail by Moradi & Floryan (2014) and thus this presentation is limited to a short outline. Consider steady and fully developed flow through a smooth straight channel extending to ±∞ in the x-direction and driven by a constant pressure gradient along the x-direction.…”
Section: Flow In a Channel With Longitudinal Groovesmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency has been increased by an order of magnitude through the development of specialized solvers which account for the special structure of the coefficient matrix [38,39]. The method has been used to identify the laminar drag-reducing grooves [16][17][18][19][20] and to study the effects of various grooves on the flow stability [40][41][42][43][44][45][46]. This work is focused on the development of an efficient algorithm suitable for the analysis of changes in the pressure gradient required to drive a specified flow rate through a vibrating channel.…”
Section: Introductionmentioning
confidence: 99%